MP20: Resuscitative thoracotomy: development of a video curriculum to teach a rare procedure. (May 2019) - Ryan, J.; Luhoway, J.; Leeper, W.; Poss, C.
Abstract : Innovation Concept : Resuscitative thoracotomy (RT) is a life-saving procedure in select trauma patients. However, RT is infrequently performed, limiting trainee exposure. In a survey of American training programs, graduating residents had performed an average of 3 RTs. There is no published data regarding the number of RTs observed and performed by Canadian trainees. We theorized that RT procedural exposure and comfort level would be low in emergency medicine (EM) trainees at our institution due to lack of exposure. Thus, we aimed to create a first person procedural video using local resources to teach RT.Methods : We first created a needs assessment survey conducted within Western University Division of Emergency Medicine over two months in 2018. Senior residents observed an average of 1.5 RT procedures and participated in an average of 0.6. Furthermore, 88% of senior residents cited a lack of confidence in their ability to perform this procedure and 87% indicated an instructional video would be a valuable educational tool. We created a video described in detail below. Prior to video distribution a survey was distributed asking respondents to list the critical steps in performing an RT. Participants were then asked to view the video and complete the survey again. Responses were scored by two independent reviewers.Curriculum, Tool or Material : An immersive cadaveric simulation video was developed in collaboration with a trauma surgeon at our institution. The video reviewed our thoracotomy tray, RT indications/contraindications, and demonstrated a narrated first-person RT on a floppy embalmed cadaver. Potential difficulties encountered during the procedure are highlighted throughout the video with troubleshooting tips suggested.Conclusion : We had 46 survey respondents from our division (25 residents and 21 consultants). After viewing the video, procedural step scores were significantly higher for junior FRCPC (p = 0.001), senior FRCPC (p = 0.013), and CCFP-EM (p < 0.001) residents as well as consultants (p = 0.016). There was also an increase in the number of respondents who reported confidence in their ability to perform RT post-video (n = 4 pre-video; n = 11 post-video). This video is an inexpensive, effective way to teach the critical procedural steps of RT and can be easily adapted for use at other institutions. Next steps for further education in this topic include development of a hands-on cadaveric simulation curriculum for residents.